Innovation as influence factor in competitiveness of brazilian textile supply chain:: the vision of managers - Caldeira, Adilson (2018)
Brazilian textile industry companies face the challenge to innovate as a condition to increase its insertion in international market and preserve spaces in local market. This study aims to identify the factors related to innovation that influence the competitiveness of member companies of the Brazilian textile productive chain according to managers who work in them. We adopted qualitative and quantitative research methods, including interviews with leaders of the class focused sector entities, in order to identify innovations practiced by their constituents. Subsequently, a questionnaire was answered by professionals from various links of the Brazilian textile sector. Through factor analysis and correlation we identified obstacles to innovate, especially the lack of funding and support for the country's competitiveness on the global stage. However, the study detected practices leading to improved competitive conditions. Results may be of interest to companies resembled those of the surveyed sample, entities that represent their classes and also to funding agents.